Preliminary Identification of Key Genes Controlling Peach Pollen Fertility Using Genome-Wide Association Study - Zhenyu Huang; Fei Shen; Yuling Chen; Ke Cao; Lirong Wang (Plants, 2021)
Previous genetic mapping helped detect a ~7.52 Mb putative genomic region for the pollen fertility trait on peach Chromosome 06 (Chr.06), which was too long for candidate gene characterization. In this study, using the whole-genome re-sequencing data of 201 peach accessions, we performed a genome-wide association study to identify key genes related to peach pollen fertility trait. The significant association peak was detected at Chr.06: 2,116,368 bp, which was in accordance with the previous genetic mapping results, but displayed largely improved precision, allowing for the identification of nine candidate genes. Among these candidates, gene PpABCG26, encoding an ATP-binding cassette G (ABCG) transporter and harboring the most significantly associated SNP (Single Nucleotide Polymorphism) marker in its coding region, was hypothesized to control peach pollen fertility/sterility based on the results of gene function comparison, gene relative expression, and nucleotide sequence analysis. The obtained results will help us to understand the genetic basis of peach pollen fertility trait, and to discover applicable markers for pre-selection in peach.